Camden after the fall : decline and renewal in a post-industrial city - Gillette, Howard, Jr., 1942- (Politics and culture in modern America., 2005)
"Looking at the cumulative effects of urban decline in the classic post-industrial city of Camden, New Jersey, historian Howard Gillette, Jr., probes the interaction of politics, economic restructuring, and racial bias to evaluate contemporary efforts at revitalization. In a sweeping analysis, Gillette identifies a number of related factors to explain this phenomenon, including the corrosive effects of concentrated poverty, environmental injustice, and a political bias that favors suburban amenity over urban reconstruction."--Jacket.